Optimizing the Approach to the Treatment of Iron-Deficiency Anemia in Children - Ye.I. Yulish (Zaslavsky O.Yu., 2015)
The paper presents the data on the prevalence and importance of iron-deficiency anemia for the health, physical and intellectual development of children of various ages. The possibilities and the best means for the correction of iron metabolism and treatment of diseases associated with iron deficiency are considered.